Resistive switching behaviour of organic molecules. (2021) - Dey, Bapi; Sarkar, Surajit; Banik, Hritinava; Arshad Hussain, Syed
Abstract: Organic electronics is very promising due to the flexibility, modifiability as well as variety of the available organic molecules. Efforts are going on to use organic materials for the realization of memory devices. In this regard resistive switching devices surely will play a key role. In this paper an effort has been made to illustrate the general information about resistive switching devices as well as switching mechanisms involving organic materials. As a whole a general overview of the emerging topic resistive switching has been given.